5-Methylhydantoin: from isolated molecules in a low-temperature argon matrix to solid state polymorphs characterization - Nogueira, Bernardo A.; Canotilho, J.; Eusebio, M. E. S.; Henriques, M. S. C.; Paixao, J. A.; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Amer Chemical Soc, 1155 16th St, Nw, Washington, Dc 20036 USA, 2017)
The molecular structure, vibrational spectra and photochemistry of 5-methylhydantoin (C4H6N2O2; 5-MH) were studied by matrix isolation infrared spectroscopy and theoretical calculations at the DFT(B3LYP)/6-311++G(d,p) theory level. The natural bond orbital (NBO) analysis approach was used to study in detail the electronic structure of the minimum energy structure of 5-MH, namely the specific characteristics of the sigma and pi electronic systems of the molecule and the stabilizing orbital interactions. UV irradiation of 5-MH isolated in argon matrix resulted in its photofragmentation through a single photochemical pathway, yielding isocyanic acid, ethanimine, and carbon monoxide, thus following a pattern already observed before for the parent hydantoin and 1-methylhydantoin molecules. The investigation of the thermal properties of 5-MH was undertaken by differential scanning calorimetry (DSC), polarized light thermal microscopy (PLTM) and Raman spectroscopy. Four different polymorphs of 5-MH were identified. The crystal structure of one of the polymorphs, for which it was possible to grow up suitable crystals, was determined by X-ray diffraction (XRD). Two of the additional polymorphs were characterized by powder XRD, which confirmed the molecules pack in different crystallographic arrangements.
Keywords: Crystal-Structures; Infrared-Spectra; Hydantoins; Photochemistry; Derivatives; Inhibitors; Density